Automation problems of switching operations planning in electrical networks - I. A. Golovinskii (Вестник Северо-Кавказского федерального университета, 2023)
The paper considers the problem of automating creation of the switching operations plans in electrical networks. The study analyzes the causes for the failures of attempts to solve it, which have been made for 40 years. Three groups of causes are specified: incompleteness of databases, insufficient formalization of switching technology, non-optimal partition of functions between participants of planning. The achieved overcoming of the first group of causes is noted; the framework for solving the problems of the second group is proposed; the third group is examined. For the second group, the article substantiates the necessity of presenting generalized sequences (scenarios) of the switching operations in a special formalized language, outside the codes of computer programs. The principles of this language and the methods of concretizing formalized scenarios are proposed.